Impact of the recent pandemic on the psychological health of the community - Maqsood, Niaz; Hassan, Summaira; Waheed, Faryal; Abbas, Syed Fakhar (Journal of Pakistan Psychiatric Society, 2020)
Introduction: The emergence of the COVID-19 and its consequences has led to fears, worries, depression and anxiety among individuals worldwide.1 Methodology: This descriptive cross sectional study was conducted through a web based questionnaire. A total of 636 participants filled the questionnaire completely from 1st April 2020 to 31st May 2020.Then the data was analyzed. Results: the frequency of depression, anxiety and disturbed sleep were 46.8%,45.2% and 51.2%. The relationship of these factors with gender was statistically significantConclusions: Psychiatric problems along with the disease itself should be addressed to uplift the health of the community.Keywords: Covid-19, depression, anxiety